LABORATORY STUDIES TO ASSESS THE DEGREE OF CONTAMINATION IN MILK (British Journal of Global Ecology and Sustainable Development, 2023)
The article analyzes the methods of general bacterial contamination of milk, which are used in assessing the quality of milk raw materials.